Oral sitafloxacin vs intravenous ceftriaxone followed by oral cefdinir for acute pyelonephritis and complicated urinary tract infection: A randomized controlled trial - Bannakij Lojanapiwat (2019)
© 2019 Lojanapiwat et al. Background: The conventional antibiotic regimen for community-acquired upper urinary tract infections with moderate severity in Thailand is parenteral ceftriaxone (CTRX) for several days followed by oral cephalosporin for 7–14 days. The aim of this study was to compare the efficacy and safety of oral sitafloxacin (STFX) with that of intravenous CTRX followed by oral cefdinir (CFDN) for the therapy of acute pyelonephritis (APN) and complicated urinary tract infection (cUTI). Methods: This open-label, randomized, controlled, noninferiority clinical trial included patients from nine centers across Thailand. Adult patients with APN or cUTI were randomly assigned to receive 100 mg of oral STFX twice daily for 7–14 days, or 2 g of intravenous CTRX for several days followed by 100 mg of oral CFDN three times per day for another 4–12 days. Results: A total of 289 adult patients with APN or cUTI (141 in the STFX group and 148 in the CTRX/CFDN group) were included in the intent-to-treat (ITT) analysis, and 211 patients (108 in the STFX group and 103 in the CTRX/CFDN group) were included in the per-protocol (PP) analysis. The baseline characteristics of patients in both groups were comparable. The causative pathogen in most patients with APN or cUTI was Escherichia coli. The clinical success rates at the end of treatment revealed the STFX regimen to be noninferior to the CTRX/CFDN regimen (86.6% vs 83.8% for ITT analysis and 97.2% vs 99.0% for PP analysis, respectively). Adverse events with mild-to-moderate severity were similar between groups. Conclusion: Oral STFX is noninferior to intravenous CTRX followed by oral CFDN in adult patients with APN and cUTI. Lower rates of resistance compared to CTRX and/or CFDN and oral administration suggest STFX as a more attractive treatment option in this patient population.